Plant layout design using Arena simulation - Võ Trọng Cang (Journal of Technical Education Science, 2012)
In the past, there were many techniques to design the layout of an industrial plant. The most popular was CRAFT (Computerize Relative Allocation Facilities Technique). However, CRAFT just finds the results based only the minimum total transfer cost between departments, but not considers other parameters such as the total time in the system, the waiting time, and utilization time. Therefore, simulation techniques in conjunction with Microsoft Visual Basic (VB) is used to develop the system of plant layout design. VB helps the designing system to connect with the Arena simulation system as well as to support the outcome report.